Answer:
This equation is invalid.
Explanation:
3(4x-1)=6(2x-5)
We simplify the equation to the form, which is simple to understand
3(4x-1)=6(2x-5)
Reorder the terms in parentheses
+(+12x-3)=6*(2x-5)
Remove unnecessary parentheses
+12x-3=+6+*(+2x-5+)
Reorder the terms in parentheses
+12x-3=+(+12x-30)
Remove unnecessary parentheses
+12x-3=+12x-30
We move all terms containing x to the left and all other terms to the right.
+12x-12x=-30+3
We simplify left and right side of the equation.
0x=-27
0=-27
The left and right sides are not equal, therefore there is no solution. This equation is invalid.